Selective targeting of MD2 attenuates intestinal inflammation and prevents neonatal necrotizing enterocolitis by suppressing TLR4 signaling - Huang, Dabin; Wang, Ping; Chen, Juncao; Li, Yanbin; Zhu, Mingwei; Tang, Yaping; Zhou, Wei (Frontiers in Immunology, 2022)
Neonatal necrotizing enterocolitis (NEC) is an inflammatory disease that occurs in premature infants and has a high mortality rate; however, the mechanisms behind this disease remain unclear. The TLR4 signaling pathway in intestinal epithelial cells, mediated by TLR4, is important for the activation of the inflammatory storm in NEC infants. Myeloid differentiation protein 2 (MD2) is a key auxiliary component of the TLR4 signaling pathway. In this study, MD2 was found to be significantly increased in intestinal tissues of NEC patients at the acute stage. We further confirmed that MD2 was upregulated in NEC rats. MD2 inhibitor (MI) pretreatment reduced the occurrence and severity of NEC in neonatal rats, inhibited the activation of NF-κB and the release of inflammatory molecules (TNF-α and IL-6), and reduced the severity of intestinal injury. MI pretreatment significantly reduced enterocyte apoptosis while also maintaining tight junction proteins, including occludin and claudin-1, and protecting intestinal mucosal permeability in NEC rats. In addition, an NEC in vitro model was established by stimulating IEC-6 enterocytes with LPS. MD2 overexpression in IEC-6 enterocytes significantly activated NF-κB. Further, both MD2 silencing and MI pretreatment inhibited the inflammatory response. Overexpression of MD2 increased damage to the IEC-6 monolayer cell barrier, while both MD2 silencing and MI pretreatment played a protective role. In conclusion, MD2 triggers an inflammatory response through the TLR4 signaling pathway, leading to intestinal mucosal injury in NEC. In addition, MI alleviates inflammation and reduces intestinal mucosal injury caused by the inflammatory response by blocking the TLR4-MD2/NF-κB signaling axis. These results suggest that inhibiting MD2 may be an important way to prevent NEC.